Glorious days and nights a jazz memoir - Snitzer, Herb (University Press of Mississippi, 2011)
A personal account of the fifty-year career of jazz photographer Herb Snitzer, with a special focus on his years in New York City from 1957 to 1964. A photojournalist for Life, Look, and Fortune, Snitzer was the photo editor and later associate editor of the influential jazz magazine Metronome.